Building communities of interest and practice through critical exchanges among chilean and colombian novice language teachers - Farias, Miguel; Obilinovic, Katica (Colombian Applied Linguistics Journal, 2009)
This article reports a collaborative experience between two groups of EFL novice teachers from Chile and Colombia. We explored the potential of a virtual platform and other means of ICT connectivity to create communities of practice and interest by engaging in critical pedagogy activities that allowed the trainees to look at their education from a comparative perspective. Through the creation of blogs, a group of 30 Chilean pre-service teachers, as language learners and language users, were asked particularly to reflect critically on the power of hypertextuality so they could gain an understanding of the (non-neutral) constructedness of texts, to raise their rhetorical awareness both as text producers and text readers, and to develop agency as communicators and not just passive receivers of media messages. We postulated that immediate feedback from peers and opportunities for sharing with real global audiences would promote higher level thinking, communication skills, and deeper understandings of texts. Sample comments taken from responses to a qualitative survey applied to the Chilean participants will be used to illustrate these points.